2013
DOI: 10.5114/wiitm.2013.39514
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic correction of the uterine muscle loss in the scar after a Caesarean section delivery.

Abstract: Caesarean section is the most frequently conducted surgery in modern obstetrics. It involves a significant risk of complications; also disorders in the area of the scar after hysterotomy may lead to menstrual disorders, pain and secondary infertility. In light of the presented facts the significance of a good uterus muscle correction method is high. We present a case of a 28-year-old patient after Caesarean section with further reproductive plans. In the ultrasonographic examination the residual thickness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Several case reports, case series and small prospective cohort studies with a maximum of 38 included women and one larger retrospective comparative study ( n  = 59) have been reported 5, 12, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35. Eleven articles (including a total of 65 women) reported a reduction or complete resolution of postmenstrual spotting; however, this was mostly not measured in a standardised way 5, 16, 18, 20, 21, 24, 26, 27, 29.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports, case series and small prospective cohort studies with a maximum of 38 included women and one larger retrospective comparative study ( n  = 59) have been reported 5, 12, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35. Eleven articles (including a total of 65 women) reported a reduction or complete resolution of postmenstrual spotting; however, this was mostly not measured in a standardised way 5, 16, 18, 20, 21, 24, 26, 27, 29.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of consensus about the best treatment choice. In our opinion, in postmenstrual bleeding disorders, when family planning is not yet concluded, surgical correction should generally be the first-line option [ 4 , 12 , 31 33 , 47 ]. The hysteroscopic isthmocele excision can only be planned when the patient does not plan further pregnancies [ 9 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are excellent reviews about all treatment methods, but there is still a lack of universal guidelines how to proceed with patients suffering from isthmocele [ 30 ]. There are no universal clinical guidelines to indicate which techniques should be preferred, or which of them gave better results in abnormal uterine bleeding, pelvic pain or secondary infertility treatment [ 4 , 30 33 ]. Almost every center uses its own indications and methods, but this does not affect overall improvement of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Algunas de las desventajas son los mayores costos, mayor tiempo operatorio, mayor pérdida sanguínea y mayor tiempo de estancia hospitalaria. Por otra parte, las ventajas descritas son la posibilidad de utilizarlo en defectos muy profundos y la posibilidad de tratar defectos que tengan una localización alta, mejor visualización del defecto, menor riesgo de daño a órgano vecino y una corta estancia hospitalaria 16,33 .…”
Section: Laparoscopiaunclassified